Drainage procedures for small duct disease in chronic pancreatitis: a feasible option - Vutukuru, Venkatarami Reddy; R. V., Raghavendra Rao; Mathai, Varughese; Settipalli, Sarala (International Surgery Journal, 2018)
Background: Surgery is the treatment of choice for intractable pain in chronic pancreatitis (CP). Drainage procedures are indicated in large duct disease whereas resectional procedures for small duct disease. Aim of this study was to assess prospectively the feasibility of drainage procedures in patients with CP with small duct disease. Methods: All consecutive patients with CP with small duct disease were included in the study. All patients underwent surgical intervention (lateral pancreaticojejunostomy with head coring). Primary outcome measures were pain relief and morbidity. These outcomes were compared with patients with CP with large duct disease. Results: 114 patients with CP underwent surgery. Of these 24(21.05%) patients had CP with small duct disease and 90(78.95%) patients had large duct disease. Demographic profile of the two groups was comparable. Mean pain scores were similar (47.75±6.85 versus 51.38±7.40; p = 0.14). Patients with large duct disease had higher incidence of diabetes mellitus (44.44% versus 8.33%; p = 0.02), but exocrine insufficiency was similar. All patients had calcifications in both the groups. Mean intraductal pressures measured intraoperatively were significantly high in patients with large duct disease (22.99±5.65 versus 18.33±3.52; p = 0.001). Frequency of complications at presentation were similar in both the groups (p = 0.29). Surgery relieved pain in 21/24 (87.5%) patients with small duct disease and 82/90 (91.11%) patients with large duct disease. Mean post-operative pain scores in small duct disease group (7.50±9.61 versus 51.38±7.40; p <0.001) and large duct disease group (5.14±7.88 versus 47.75±6.85; p <0.001) were significantly reduced when compared to preoperative pain scores. Incidence of postoperative complications was similar in both groups (16.66% versus 14.44%). Conclusions: Drainage procedures (lateral pancreaticojejunostomy with head coring) is a feasible for CP patients with small duct disease with good pain relief.